The soft side of hard metrics: Lessons from software development in multinational organizations - Lindström, Nataliya Berbyuk; Asatiani, Aleksandre; Mankevich, Vasili; Zhang, Yixin (Business horizons, 2025)
Software metrics are widely used in agile development to enhance productivity, quality, and decision-making. However, their effectiveness is often hindered by communication challenges that arise from differing stakeholder perspectives, organizational structures, and the social dynamics of software teams. This paper explores these challenges through an empirical study of four multinational industrial organizations in Sweden and Germany. We identify key obstacles, including a lack of shared understanding of metrics, unclear stakeholder roles, ineffective communication channels, and the unintended use of metrics as tools for criticism rather than improvement. Based on our findings, we propose a framework of best practices to enhance metrics communication, foster transparency, and ensure that metrics support constructive feedback rather than causing resistance. By addressing the human factors in software measurement, organizations can improve collaboration, decision-making, and the overall positive impact of their metrics programs.